HEIDEGGER, Martin. Contribuições à filosofia: do Acontecimento apropriador. - Bosco Batista, João (Revista Estudos Filosóficos - UFSJ, 2017)
HEIDEGGER, Martin. Contribuições à filosofia: do Acontecimento apropriador. Tradução de Marco Antônio Casanova. Revisão de Gabriel Lago Barroso. Rio de Janeiro: Via Vérita, 2015, 503 p.